Reabilitação da deglutição: tempo e fatores prognósticos em pacientes disfágicos hospitalizados - Menezes, Fernanda Teixeira [UNIFESP] (2010)
Purpose: To analyze the average number of swallowing rehabilitation sessions necessary for the release of oral intake, at least one consistency, and the factors that influenced the number of swallowing rehabilitation sessions. Methods: An observational, analytical and retrospective study of 260 dysphagic patients with different diagnosis, neurological or not, at the São Paulo Hospital (UNIFESP), ages between 02 and 105 years, evaluated and treated by Speech and Language Integrated Service among August / 2007 and August/2009. Results: The average number of swallowing sessions necessary for the release of oral intake was 4.13 sessions. The factors that contributed to a significantly higher number of rehabilitation sessions were male gender, duration of hospital stay, time to request initial bedside swallowing evaluation; time of tube feeding, pneumonia, sepsis, duration of intubation, reintubation, duration of tracheotomy, duration of mechanical ventilation, duration of nebulization, swallowing saliva impairment, voice impairment, reduction of laryngeal elevation and supraglottic penetration. Regression analysis showed that the combination of the following factors interfered in the number of swallowing rehabilitation sessions: swallowing saliva impairment associated with voice impairment, swallowing saliva impairment associated with reduced laryngeal elevation and swallowing saliva impairment associated with time to request initial bedside swallowing evaluation. Conclusions: The average number of sessions to release oral intake was 4.13, which corresponds to about 5 days. Were identified 15 factors that caused the delay to release the oral intake. However, the rehabilitation of swallowing showed significant improvement in these patients.